2021
DOI: 10.1007/s13730-021-00598-7
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin and Colchicine combined myotoxicity: lessons to be learnt

Abstract: Statins and colchicine co-administration consists of a potentially catastrophic drug-drug interaction since it provokes myotoxicity, myopathy and various degrees of rhabdomyolysis. Lipophilic statins and colchicine are biotransformed in the liver, primarily via CYP3A4 enzyme system leading to elevated blood levels of both agents and resulting in increased potential for combined myotoxicity. Hence, it would be of great clinical importance not only the awareness of this devastating complication but also the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Administration of RSV was reported to cause proximal tubule damage and renal toxicity in rats [ 35 ] and acute interstitial nephritis in humans [ 36 ]. In addition, RSV caused renal damage associated with severe rhabdomyolysis, whether RSV was given alone [ 37 , 38 , 39 ], or in combination with colchicine [ 40 ], ticagrelor [ 41 ], or cocaine and heroin [ 42 ]. Despite that the results of the current study suggested that RSV had protective effects against DN, long-term follow-up studies are needed to confirm whether RSV improves DN or just delays its progress.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of RSV was reported to cause proximal tubule damage and renal toxicity in rats [ 35 ] and acute interstitial nephritis in humans [ 36 ]. In addition, RSV caused renal damage associated with severe rhabdomyolysis, whether RSV was given alone [ 37 , 38 , 39 ], or in combination with colchicine [ 40 ], ticagrelor [ 41 ], or cocaine and heroin [ 42 ]. Despite that the results of the current study suggested that RSV had protective effects against DN, long-term follow-up studies are needed to confirm whether RSV improves DN or just delays its progress.…”
Section: Discussionmentioning
confidence: 99%
“…15 Published case reports and observational studies of colchicine when given concomitantly with inhibitors of CYP3A4/P-gp point to the clinical relevance of these interactions. 9,16-18 Patients with chronic conditions are often exposed to polypharmacy making relevant drug-drug interaction (DDI) information crucial for safe therapy. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…15 Published case reports and observational studies of colchicine when given concomitantly with inhibitors of CYP3A4/P-gp point to the clinical relevance of these interactions. 9,[16][17][18] Patients with chronic conditions are often exposed to polypharmacy making relevant drug-drug interaction (DDI) information crucial for safe therapy. 19,20 The purpose of this study analysis was to identify potential clinical implications of exposure to colchicine and CYP3A4/P-gp inhibitors using spontaneously submitted safety reports present in the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS).…”
Section: Introductionmentioning
confidence: 99%